Efficacy of laser stimulation of the retina with subsequent nutrient supplementation for treatment of asthenopia in students (Ukrainian Journal of Ophthalmology, 2026)
Background. Asthenopia is a key point in information fatigue syndrome. The incidence of asthenopia syndromes (one or several) among students is 57-89.9%. The recent data have evidenced that dietary supplements with a combination of omega-3 fatty acid, bilberry extract and lutein reduce asthenopia symptoms.Purpose. The purpose was to assess the efficacy of a course of laser stimulation of the retina with a subsequent nutrient supplementation in students with asthenopia.Material and Methods. We performed comprehensive examination of 36 students (72 eyes), aged 18 to 25, with asthenopia signs. There were two groups: group 1, 19 students (38 eyes); group 2, 17 students (34 eyes). All study eyes underwent 10 every-day sessions of diode laser stimulation of the retina (LSR) (wavelength, 650 nm; irradiance, 0.4 mW/sm²; treatment timing, 300 s). On completion of a course of  LSR, the students of group 2 were recommended a Nutrof®Total vitaminous antioxidant complex, one capsule daily for 6 months.Results. A course of laser stimulation of the retina and a 6 month nutrient supplementation for asthenopia students made it possible to improve visual acuity by 12% in 91 % of the students, to recover the reserves of accommodation over 3 D in 73% of the students, to improve the vascular tone by 34% in 59% of the students and light sensitivity of retinal cones by 25% in 82% of the students; asthenopia graded from moderate to mild in 91% of the students; the overall emotional state was normalized in all students by 37% according to a HADS scale. Conclusions. A course of LSR and a 6 month nutrient supplementation enables to improve students’ overall health and professional activity while reduced asthenopia creates conditions for health improvement, better quality of studying and open career opportunities.
Keywords: asthenopia in students; laser stimulation of the retina; nutrient supplementation